CONCEPT AND MEANS OF FORMALIZING ACTIVITIES IN THE FIELD OF CRIMINAL JUSTICE - Oleksandr Khan (Вісник Харківського національного університету імені В. Н. Каразіна Серія: «Право»)
Introduction. At the current stage of development of criminal procedure and forensic science, the sphere of criminal justice is often considered from the perspective of an activity-based approach, i.e., as the activities of individual subjects (investigator, prosecutor, suspect (accused), defense counsel, investigating judge, court, etc.) and their interaction. Similarly, a large number of proposals in the literature are related to the improvement or optimization of their activities with regard to the general principles of criminal proceedings. This article is no exception and is aimed at clarifying the approaches to understanding the activities in the field of criminal justice and their regulation (formalization).